Gender equality and welfare politics in Scandinavia : the limits of political ambition? - Melby, Kari; Ravn, Anna-Birte; Wetterberg, Christina Carlsson, 1950- (Policy Press, 2008)
"Gender equality is often seen as a hallmark of the Nordic countries. This book explores this notion by examining the meanings of gender that underpin policies in the Scandinavian welfare states, historically and today. The book focuses on three Scandinavian countries - Denmark, Norway and Sweden - and explores the policy reforms that have occurred relating to family and care. Beginning with the radical marriage reform carried through in all the three countries in the early decades of the 20th century, the book progresses to explore contemporary challenges to the traditional model of equality, including equal rights for fathers, multiculturalism and a critical young generation. The book focuses on differences as well as similarities between the countries and discusses the relevance of talking about a Nordic model. Stressing the importance of viewing the concept of equality in its historical context, the book critically investigates and discusses the Scandinavian 'success story' portrayed in normative political theory and presents an historical analysis of the development of gendered citizenship rights. It will be a valuable collection for researchers, lecturers and graduate students who work with historical and contemporary studies on welfare state and gender models from different disciplinary or interdisciplinary perspectives"--Provided by publisher